The The Role of Pastors in the Implementation of Service Supervision to Improve the Quality of Service in the AI Century - Waruwu, Sabarani; Andar Gunawan Pasaribu (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This article discusses the important role of pastors in improving the quality of church services in the digital era, especially through good supervision and the use of technology such as artificial intelligence (AI). Amidst the challenges of the 21st century, pastors not only deliver the word of God, but must also be able to lead and manage the church relevantly and effectively. This study uses a literature study method with a qualitative approach, to see how pastors can adjust their supervision methods to the changing times. The results show that pastors have two main roles: as spiritual leaders and also as organizational managers. They need to have leadership skills, conflict management, staff development, and the ability to adapt to technology. The use of AI can help more appropriate supervision, for example in understanding the needs of the congregation, composing sermons, and fostering the congregation more personally. However, AI cannot replace human relationships and the empathetic presence of pastors. In addition, the use of AI also faces challenges such as rejection from some church leaders and the need for training. This article offers strategies so that pastors can combine technology wisely without abandoning spiritual values, so that church services remain strong, relevant, and touch the lives of the congregation in this digital era.